DARI PASAL KARET KE KEPASTIAN HUKUM: PERJALANAN UU ITE INDONESIA 2008-2026 - Uly Wali Daturrahmah; Harmonis (DECODING: Jurnal Mahasiswa KPI, 2026)
Since its enactment in 2008, the Information and Electronic Transactions Law (ITE Law) has served as the legal foundation for digital activities in Indonesia, yet its articles have often been criticized as multi-interpretive and potentially silencing freedom of expression. This study aims to analyze the dynamics of changes to the ITE Law from 2008 to 2026 and examine the 2025 Constitutional Court decision that narrows problematic articles. This research employs a descriptive qualitative approach with literature study method and thematic analysis. The findings reveal four main themes: the journey of regulatory changes, the Constitutional Court decision as a turning point, harmonization with the new Criminal Code, and implementation challenges at the law enforcement level. This study concludes that although regulations continue to be improved, implementation challenges still trigger a chilling effect on public freedom of expression.